Antimicrobial, antioxidant activity of ethyl acetate extract of Streptomyces sp. PERM2, its potential modes of action and bioactive compounds - Peguy Flora Djuidje, Kouomou; Esperanza Ghomsi, Guiadem; Maurice Fotsing, Tagatsing; Wong, Mui-Yong; Carole, Beaulieu; Cecile Annie, Ewane; Thaddee, Boudjeko (Heighten Science Publications, 2024)
Background: Microorganisms belonging to Streptomyces sp. are Gram-positive bacteria known for their unsurpassed capacity for the production of secondary metabolites with diverse biological activities. The aim of this study was to evaluate the antimicrobial and antioxidant properties of ethyl acetate Streptomyces sp. PERM2 extract, its potential modes of action and bioactive secondary metabolites.